Emilio Duhau. Mercado interno y urbanización en el México colonial. México : UAM : Ternika, 1988. 306 p. - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1989)
EMILIO DUHAU, Mercado interno y urbanización en el México colonial UAM-Ternika, México, 1988.